Partisipasi Masyarakat Dalam Pengembangan Objek Wisata Gubug Serut di Desa Persen - Ayu Puspita; Tri Suminar (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to describe the form of community participation in developing the Gubug Serut tourist attraction in Desa Persen and its impacts. This research uses descriptive qualitative methods with data collection techniques through observation, interviews and documentation. The data sources used by researchers are primary data and secondary data. The results of this research show that there are four forms of community participation in the development of the Gubug Serut tourist attraction in Desa Persen, namely in the form of participation in decision making, participation in implementation, participation in taking benefits, and participation in evaluation. Community participation in the development of the Gubug Serut tourist attraction has had an impact on the social and economic fields.